The Usage of ICT in The Classrooms of Primary School - Baydullayeva Firuza Akilbekovna (Research Parks Publishing LLC, 2021)
Traditionally, it is believed that a child receives literacy in primary school, where he is taught to write, read and count. This is undoubtedly the case. But modern society needs new ways of activity, which requires a person to develop a whole range of skills and abilities - finding the necessary information, processing it, providing it to other people, modeling new objects and processes, self-planning and building their actions. Along with teaching reading, writing and numeracy skills, starting from the first grade, it is important to teach children how to use digital technology as a working tool in their studies and everyday life